2018
DOI: 10.3920/cep180021
|View full text |Cite
|
Sign up to set email alerts
|

Reducing peak pressures under the saddle at thoracic vertebrae 10-13 is associated with alteration in jump kinematics

Abstract: There is little information about horse-saddle interaction at take-off for a fence, although there is potential that this could have an influence on performance. It was hypothesised that (1) maximum peak pressure under the saddle would occur in the phase of maximum thoracolumbar flexion prior to hindlimb take-off; and (2) limb and trunk kinematics at take-off over the fence would be affected by reducing peak pressure at Thoracic vertebrae (T)10-13 at the point in the stride where peak pressures occur. The peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The cranial region of the thoracic spine (T10–T13) is of great interest; it is where the rider’s centre of mass aligns approximately above the horse’s centre of mass. It is the area where the saddle is at its narrowest and it is also a region that has been reported to be associated with muscle activity [36] and improved gait features when saddle pressure in this region was reduced after modified saddle design [15,26]. Increased amplitudes have been reported in the dorsoventral ROM occurring at T13 compared with T18 and L3 in non-lame horses trotting in a straight line [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cranial region of the thoracic spine (T10–T13) is of great interest; it is where the rider’s centre of mass aligns approximately above the horse’s centre of mass. It is the area where the saddle is at its narrowest and it is also a region that has been reported to be associated with muscle activity [36] and improved gait features when saddle pressure in this region was reduced after modified saddle design [15,26]. Increased amplitudes have been reported in the dorsoventral ROM occurring at T13 compared with T18 and L3 in non-lame horses trotting in a straight line [37].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further support that saddle width has an effect on the thoracolumbar spine arises from our thoracolumbar dimensions. The thoracolumbar musculature has been reported to change over a year as a result of changes in body weight, seasonal variations, and saddle fit [30], as well as after thirty minutes of exercise when horses are worked correctly in a well fitted saddle [29], and also after modifications of the saddle resulting in reduced saddle pressures in the thoracic region [15,26]. In the current study, smaller epaxial musculature dimensions were found at T13 after ridden exercise in the wide saddle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The saddle is an essential piece of equipment coupling the horse and rider. The effects of saddle fit [ 1 , 2 , 3 ] and saddle design [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] on equine health and performance are becoming better understood. Incorrect saddle fit is thought to be a potential contributing factor in the context of back problems, poor attitude to work and poor performance [ 3 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%